Interações entre xonobióticos e bioestimulante na fisiologia da soja sob défict hídrico - Schneider, Julia Renata (2022)
Plants develop in field conditions exposed to environmental conditions, biotic or abiotic stressors. In this study we evaluated the influence of water deficit combined with the application of xenobiotic products on the physiological relationships and antioxidant metabolism of soybean. Furthermore, we tested the efficiency of a biostimulant, as a stress reliever mitigating symptoms triggered by stress. The experiments were conducted in a controlled environment, to eliminate interactions of other stressors, in a growth chamber, with controlled temperature, humidity and luminosity. Water deficit and exposure to xenobiotics are stressors that occur simultaneously during the development of the crop, and may be responsible for generating oxidative stress, when there is an imbalance between the production of reactive oxygen species, and the antioxidant compounds of plant defense. This situation, depending on which intensity occurs, generates several changes in metabolism, including damage at the cellular and molecular levels. In this study we observed that the combination of water deficit with the xenobiotic mancozeb did not cause deleterious effects. The xenobiotics applied in this study increased plant metabolism under irrigated conditions, indicating that in addition to their fungicidal function, they can bring other indirect benefits. Water deficit triggered the accumulation of reactive oxygen species in cells, which caused damage to membranes, and lipid peroxidation, increased activity of enzymes and antioxidant compounds, and increased concentration of proline and nitric oxide. Proline also accumulated in the cells of plants treated with the biostimulant, which indicates its role as a defense inducer in these stressed plants. The biostimulant compound was also responsible for activating the plant's antioxidant metabolism, which is extremely important, since the plant recovers its metabolism long before it is affected, preventing damage, and avoiding the spent in this recovery, energy that will be demanded for grain production, avoiding loss of productivity. Combination of xenobiotic and biostimulant could be used.